Group Testing with Error-Correction Capability for General Pandemics. Issue 30 (2022) - Greferath, Marcus; Rößing, Cornelia
Abstract: Based on a recently presented approach to non-adaptive group testing in terms of residuated pairs on Boolean lattices, we extend our investigation into group testing to the noisy case. In this context, several concepts and techniques from traditional Coding Theory over finite fields need to be adapted and refined. We will touch a variety of relevant notions and concepts and provide some first sporadic examples of error-correcting group testing schemes. The possible applications are diverse and reach from simple search of defective items in production chains to mass testing under pandemic conditions.